MODIFICATION OF THE AMINO ACID DERIVATIVES OF COUMARINS BY 10-HYDROXYDECAHYDROISOQUINOLINE: UDC 547.466+547.814 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Based on previously synthesized coumarin amino acids, using the method of activated esters a number of new, undescribed in the literature derivatives, modified by conformationally complicated 10-hydroxydecahydroisoquinoline, were obtained.
Keywords: coumarins, amino acids, method of activated esters